The value of bluer skies: How much do consumers gain from entry by JetBlue Airways in long-haul US Airline Markets? - Kai Hüschelrath; Kathrin Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
The paper estimates the effects of entry by low-cost carrier JetBlue Airways in long-haul domestic U.S. airline markets. For the period from 2000 to 2009, we find that non-stop fares were on average about 21 percent lower post-entry; however, the magnitude of the price effect depends on the pre-entry market structure. While entry into monopoly markets triggered an average price decrease of about 25 percent, the respective average price drop for entries into oligopoly markets lied at about 15 percent. Based on additional estimates of the price and income elasticities for long-haul domestic U.S. flights, we conclude that JetBlue's long-haul entries alone led to an increase in consumer welfare of about USD 661 million.
urn:nbn:de:bsz:180-madoc-326241
Keywords: L40; L93; 330; airline industry; entry; low-cost carrier; consumer welfare effects; Luftverkehrsgesellschaft; Markteintritt; Passagierluftfahrt; Fahrpreis; Niedrigpreisstrategie; Konsumentenrente; USA